In-situ toughened CFRP composites by shear-calender orientation and fiber-bundle filtration of PA microparticles at prepreg interlayer. (May 2016) - Liu, Dawei; Li, Gang; Li, Bo; Luan, Yihao; Ling, Hui; Yang, Xiaoping
Abstract: Epoxy matrix toughened by polyethersulfone (PES) and polyamide (PA) microparticles was designed and the in-situ interlaminar toughened carbon fiber/epoxy composites were fabricated. Synergistic toughening effect of PES and PA on epoxy matrix was achieved due to semi-IPN structure of PES toughened matrix and uniform dispersion of PA microparticles. Shear-calender orientation of PA microparticles was found during prepreg processing and the microparticles remained on the surface of prepreg due to fiber-bundle filtration. The in-situ formed toughening interlayer of PA microparticles and interfacial bonding between PA and epoxy matrix were detected, which resulted in enhanced fracture toughness, CAI, and transverse flexural strength of the composite based on the PES/PA synergistically toughened matrix. SEM images of fracture morphology of the composite showed evidence of enhanced plastic deformation created by PES and PA, and crack deflection and bridging by PA microparticles.